THE ROLE OF LEVERAGE IN MEDIATION THE EFFECT OF PROFITABILITY ON FINANCIAL DISTRESS - Nurfina Sari; Fitriyah Fitriyah (JPIM (Jurnal Penelitian Ilmu Manajemen), 2022)
The motivation behind this review is to decide on the direct and indirect effects of financial distress by using profitability as an intervening variable. The sample used is 38 companies in the manufacturing sector on the IDX for the 2018-2020 periode. Sampling technique used is purposive sampling technique. The tool used for data analysis in this study is SmartPls version 3. The results of this study are profitability has a positive and significant effect on financial distress, profitability has a negative and insignificant effect on leverage, leverage has a negative and significant effect on financial distress, leverage can not mediate of profitability on financial distress.